Impact of Pancasila Ideology for Millennial Generation - Ajat Sudrajat (LEGAL BRIEF, 2022)
In making the millennial generation with high character and insight, it is necessary to implement Pancasila values according to their abilities. In addition, Pancasila will also be used as a unifying medium for the millennial generation in carrying out their various daily activities, so it is fitting for this generation to have a strong and highly integrated character, especially in facing various challenges and obstacles caused by the flow of globalization. This research is a type of qualitative research, using descriptive method. As for the goal to be achieved in this research, it is to find out the extent of the impact of Pancasila ideology on the millennial generation, the results of this study explain that, to create a millennial generation with good character, it is necessary to practice Pancasila values that are in accordance with the mindset and the personality that exists in this generation, because as we previously knew, this millennial generation is very much needed for the process of progress and growth of the nation and state, especially in understanding the various characteristics and norms that exist, so it will be easy to shape the character of the generation. On the other hand, the importance of Pancasila as the state ideology is to show how Pancasila can be a moral guide in the life of the nation and state so that threats that come from outside can be prevented quickly, because the position of Pancasila is an ideology that is open to all developments of the times, so that whatever happens In the development of the times, it must be in accordance with the rules that apply in the body of Pancasila.